Joachim of Fiore in the face of 12th-century speculative theology - Grzeszczak, Jan (Filozofia Chrześcijańska, 2019)
In one of his main works, Concordia Novi ac Veteris Testamenti, Joachim of Fiore (1135-1202) interprets the story of the biblical Lot, shown in chapter 19 of Genesis. Using in practice the method of compliance (concordia) of the Old and New Testaments and an extensive theory of biblical meanings, he sees in the degenerated inhabitants of Sodom the announcement of medieval dialects. The negative attitude of the Abbot of Fiore (Calabrian Abbot) to speculative theology results from his apocalyptic vision of history, in which the key role is played by spiritual men (viri spiritales), who herald the Holy Spirit era. According to Joachim of Fiore, self-confi dent and self-based dialectics are destructive, diverting attention from the coming apocalypse. Stuck in a letter, they do not achieve the spiritual understanding (intelligentia spiritualis) of the Bible and prevent others from doing so. The interpretation of Lot’s story by Joachim of Fiore reveals the twelfth-century intellectual climate as monastic theology gradually gives way to scholasticism practiced in cities.